Long‐Term Generation of Longitudinal Spin Order Controlled by Ammonia Ligation Enables Rapid SABRE Hyperpolarized 2D NMR. Issue 12 (17th June 2021) - Vaneeckhaute, Ewoud; De Ridder, Sophie; Tyburn, Jean‐Max; Kempf, James G.; Taulelle, Francis; Martens, Johan A.; Breynaert, Eric
Abstract: The front cover artwork front cover artwork is provided by NMRCoRe, the Flemish NMR/X‐Ray platform for Convergence Research and was designed by Ir. Ewoud Vaneeckhaute and Dr. Eric Breynaert. The image shows the reciprocity between parahydrogen, deuterated ammonia and iridium allowing for hyperpolarized 2D NMR via long‐term availability of longitudinal spin order. Read the full text of the Article at 10.1002/cphc.202100079 . Abstract : "Inspired by the SABRE‐RELAY method, we show how controlled catalyst design with deuterated ammonia, in situ generated at low‐field in a protic reaction medium, enables generating hydride asymmetry with long‐lasting observable hyperpolarization at high field…" This and more about the story behind the front cover can be found in the Article at 10.1002/cphc.202100079 .